2007
DOI: 10.4103/0970-9371.42091
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bronchial brushings and trans-bronchial needle aspiration in diagnosing carcinoma lung

Abstract: Bronchial brushing (BB) and the more recent trans-bronchial needle aspiration (TBNA) are well established techniques performed using flexible fiberoptic bronchoscope, for sampling trachobronchial lesions suspected of malignancy. Our aim was to assess the efficacy of these two techniques in diagnosing carcinoma lung, when used individually as well as in combination, taking bronchial biopsy as the "Gold Standard" diagnostic test. Of all the cases of suspected lung cancer received between 1 st January 2003 to 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…Patients in this study were slightly younger with average age 60 in female and 63 in male. The youngest was 39-year-old patient, similar to data in previous investigations 12 . Although the gender distribution of lung cancer patients is equal in developed countries, there were three times more male than female in this study, as it was in other developing countries 10,11,13,14 .…”
Section: Discussionsupporting
confidence: 89%
“…Patients in this study were slightly younger with average age 60 in female and 63 in male. The youngest was 39-year-old patient, similar to data in previous investigations 12 . Although the gender distribution of lung cancer patients is equal in developed countries, there were three times more male than female in this study, as it was in other developing countries 10,11,13,14 .…”
Section: Discussionsupporting
confidence: 89%
“…This result was also in agreement with other studies. [11][12][13] While Shah et al 27 reported the mean age of their patients with bronchial carcinoma was 45.6 years which was lower than the present study and Santos-Martínez et al 14 reported that the mean age was 67.1 (± 11.1), which was higher than the present study In this study 252 (84%) patients were male and 48 (16%) patients were female. Male were more frequently affected by bronchial carcinoma than that of female.…”
Section: Discussioncontrasting
confidence: 57%
“…Bronchial brushing (BB) is a well-established method of obtaining airway cells for analysis by dislodging them with a brush in conjunction with fiberoptic bronchoscopy. 8 Although BB samples are a valuable source of primary airway cells for research, the sample size is typically very limited (0.8–3.6 × 10 4 cells). 9 The small sample size is further complicated by the specimen heterogeneity which in addition to the intact airway epithelia contains mucus, stromal tissue, and the remnants of cells killed during dislodging.…”
Section: Introductionmentioning
confidence: 99%